Acute Histopathologic Findings Related to Needle Puncture Trauma during Subcutaneous Injection in the Sprague-Dawley Rat Model. (January 2019) - Ramot, Yuval; Kannan, Kamala; Reddy, Sathish; Krishnappa, H.; Dillberger, John E.; Nyska, Abraham
It is important to detect injection site reactions during the nonclinical phases of drug development. However, differentiating between normal changes following needle trauma and changes due to the toxicity of injected drugs can be challenging. Therefore, we used the Sprague-Dawley rat model to evaluate the pathological findings expected following a single subcutaneous injection of normal saline. Rats were subcutaneously administered with normal saline, and the injection sites were examined microscopically. Inflammation was evident in most of the injection sites, mostly in minimal severity. Parakeratosis/epithelial crust was also seen in several sites, and necrosis was observed in a minority of the cases. These findings indicate that needle puncture trauma can present with some degree of inflammation and necrosis. Although limited to a specific time point and strain, this study shows that inflammation following subcutaneous injection can be attributed in part to the needle trauma and not necessarily to the drug itself.